Effects of smoking and gingival inflammation on salivary antioxidant capacity - Nurcan Buduneli (journal of clinical periodontology, 2006)
Aim: This study evaluated possible effects of smoking and gingival inflammation on salivary antioxidants in gingivitis patients. Methods: Twenty otherwise healthy gingivitis patients (10 self-reported smokers) and 20 periodontally and systemically healthy volunteer subjects were enrolled in the study. Whole saliva samples and full-mouth clinical periodontal recordings were obtained at baseline and one month following initial phase of treatment in gingivitis patients. Salivary cotinine, glutathione and ascorbic acid concentrations, and total antioxidant capacity were determined, and the data generated were tested by nonparametric tests. Results: Salivary cotinine measurements resulted in re-classification of three selfreported non-smokers as smokers. Smoker patients revealed significantly higher probing depths but lower bleeding values than non-smoker patients (p50.044 and 0.001, respectively). Significant reductions in clinical recordings were obtained in nonsmoker (all po0.05) and smoker (all po0.01) patients following periodontal treatment. Salivary total glutathione concentrations were reduced following therapy in gingivitis patients who smoke (po0.01). Otherwise, no statistically significant differences were found between the groups in biochemical parameters at baseline or following treatment (p40.05). Conclusions: Within the limits of this study, neither smoking nor gingival inflammation compromised the antioxidant capacity of saliva in systemically healthy gingivitis patients.